Dance Gesture Recognition Using Laban Movement Analysis with J48 Classification - Joko Sutopo; Mohd Khanapi Abd Ghani; M. A. Burhanuddin; Tundo Tundo; Aulia Nur Septiani (IAES Indonesian Section, 2023)
This study describes the introduction of classical dance movements using the Laban Movement Analysis (LMA) method which consists of 3 main components, namely Body, Space, and Shape. How to carry out the classical motion recognition process using Kinect which is then read by the screen using the Brekel Kinect and produces dance motion pictures in different formats (. * BVH). After that, it is calculated using the LMA method by obtaining the results obtained in the form of numerical data from each joint from the direction of the axis (xyz), then classification is carried out using the J48 classification method provided at WEKA tools after 50 training data is carried out. 96% truth is recognized, because it guarantees those who meet the requirements, 12 data tests are carried out apart from training data, which can be 92% accurate on average, so it is very possible that this method can be used in dance preparation, especially in classical dance.